Pre-harvest spraying of oxalic acid improves postharvest quality associated with increase in ascorbic acid and regulation of ethanol fermentation in kiwifruit cv. Bruno during storage - Maratab Ali; Meng-meng LIU; Zhen-e WANG; Sheng-e LI; Tian-jia JIANG; Xiao-lin ZHENG (Journal of Integrative Agriculture, 2019)
The kiwifruit trees (Actinidia deliciosa cv. Bruno) were sprayed with 5 mmol L–1 oxalic acid (OA) or water (as control) at 130, 137 or 144 d after full-blossom, and then the fruit were harvested at commercial maturity and stored at room temperature (20±1)°C for 13 d. The effect of pre-harvest spraying of OA on postharvest quality of kiwifruit was evaluated during storage. The OA spraying slowed the increase in soluble solids content (SSC) and decrease in titratable acid (TA), as well as increased contents of ascorbic acid (AsA) and total-AsA accompanied with higher AsA/DHA ratio in kiwifruit during storage. Moreover, the OA spraying significantly reduced the contents of acetaldehyde and ethanol in kiwifruit, along with significant decrease in activities of enzymes involved in ethanol fermentation metabolism during the later period of storage, which was beneficial to control off-flavor associated with over accumulation of ethanol during postharvest. It was suggested that pre-harvest spraying of OA might maintain the postharvest quality of kiwifruit in relation to delay in fruit ripening, AsA maintenance and regulation of ethanol fermentation.